All Electrospray Printing of Carbon‐Based Cost‐Effective Perovskite Solar Cells. (4th November 2020) - Wu, Congcong; Wang, Kai; Jiang, Yuanyuan; Yang, Dong; Hou, Yuchen; Ye, Tao; Han, Chan Su; Chi, Bo; Zhao, Li; Wang, Shimin; Deng, Weiwei; Priya, Shashank
Abstract: With the power conversion efficiencies of perovskite solar cells (PSCs) exceeding 25%, the PSCs are a step closer to initial industrialization. Prior to transferring from laboratory fabrication to industrial manufacturing, issues such as scalability, material cost, and production line compatibility that significantly impact the manufacturing remain to be addressed. Here, breakthroughs on all these fronts are reported. Carbon‐based PSCs with architecture fluorine doped tin oxide (FTO)/electron transport layer/perovskite/carbon, that eliminate the need for the hole transport layer and noble metal electrode, provide ultralow‐cost configuration. This PSC architecture is manufactured using a scalable and industrially compatible electrospray (ES) technique, which enables continuous printing of all the cell layers. The ES deposited electron transport layer and perovskite layer exhibit properties comparable to that of the laboratory‐scale spin coating method. The ES deposited carbon electrode layer exhibits superior conductivity and interfacial microstructure in comparison to films synthesized using the conventional doctor blading technique. As a result, the fully ES printed carbon‐based PSCs show a record 14.41% power conversion efficiency, rivaling the state‐of‐the‐art hole transporter‐free PSCs. These results will immediately have an impact on the scalable production of PSCs. Abstract : An electrospray printing technique is developed to continuously print the TiO2 electron transport layer, perovskite layer, and carbon layer, enabling a cost‐effective device. The electrospray technique is capable of printing uniform, compact, and high adhesion layers with controllable dimensions and patterns. This work demonstrates a fully printed low‐cost solar cell and provides a feasible process for perovskite solar cells to initial industrialization.